1995
DOI: 10.1017/s0950268800058386
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and genetic location of non-transferable trimethoprim resistant dihydrofolate reductase genes in South African commensal faecal isolates

Abstract: SUMAIARYIn a recent survey of trimethoprim resistance, 357 Gram-negative aerobic organisms were isolated from healthy volunteers from rural and urban populations in South Africa. Trimethoprim resistance did not transfer to an Escherichia coli J62-2 recipient strain by conjugation in a liquid mating in 161 (45 1 %) of the isolates. These isolates which did not transfer their resistance were probed with intragenic oligonucleotide probes for the types Ia, Ib, Illa, V, VI, VII, VIII, IX, X and XII dihydrofolate re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…However, a significant number of isolates harboured a dfrA14 gene, encoding a DHFR‐Ib enzyme, which has biochemical properties similar to those of DHFR‐I, to which it is thought to be related. To our knowledge, this is the first report of dfrA14 in Shigella spp., although this gene has been shown previously to be quite common in other Enterobacteriaceae [16,17]. Other, less common, types of dfr gene were also detected ( dfrA5 , dfrA15 , dfrA12 and dfrA7 ), all as cassettes within type I integrons (unpublished data).…”
Section: Resistance Profiles Of Shigella Spp Isolated From Patients mentioning
confidence: 56%
“…However, a significant number of isolates harboured a dfrA14 gene, encoding a DHFR‐Ib enzyme, which has biochemical properties similar to those of DHFR‐I, to which it is thought to be related. To our knowledge, this is the first report of dfrA14 in Shigella spp., although this gene has been shown previously to be quite common in other Enterobacteriaceae [16,17]. Other, less common, types of dfr gene were also detected ( dfrA5 , dfrA15 , dfrA12 and dfrA7 ), all as cassettes within type I integrons (unpublished data).…”
Section: Resistance Profiles Of Shigella Spp Isolated From Patients mentioning
confidence: 56%
“…Discrimination between resistant DHFR genes within close phylogenetic groups has often been hampered by the use of gene probes which are not representative of regions of adequate heterogeneity (52). The gene probing strategy used with the collection of isolates in this study (3,4) targets gene regions which encode putative regions of low structural and functional significance. These regions are therefore most likely to be susceptible to genetic drift and therefore useful for the detection and discrimination of new gene types.…”
Section: Discussionmentioning
confidence: 99%
“…In a survey of trimethoprim resistance in South Africa, 357 isolates of gram-negative aerobic commensal fecal flora were probed with oligonucleotide probes to determine the prevalence within the population of DHFR genes that encode trimethoprim resistance (3,4). An isolate from these studies which expressed high-level trimethoprim resistance (MIC, Ն1,024 mg/liter) and which did not hybridize to any of the DHFR probes was selected for further study.…”
mentioning
confidence: 99%
“…Molecular epidemiology of dfrXV. Dot blotting was performed as described previously (3). The nucleotide sequences of dfrI and dfrXV were aligned to determine regions of maximum heterogeneity, and a 30-mer oligonucleotide probe (5Ј-ATACATTCTCATCACTGGAAGTGAAGCTTG-3Ј) which contained nine nucleotide mismatches compared with the sequence of dfrI was selected for the detection of dfrXV (boldface type in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of these enzymes have been found as gene cassettes inserted into the recombinationally active sites of integrons (22). In a survey of trimethoprim resistance in South Africa, 357 isolates of gramnegative, aerobic, commensal fecal flora were probed with oligonucleotide probes to determine the prevalence of DHFR resistance genes within the population (2,3). Hybridization experiments revealed that contrary to all previous data, the most prevalent DHFR was type Ib (21.8%), followed by types VII (18.8%), I (14.6%), VIII (12.9%), XIII (12.3%), V (7.8%), and XII (0.3%) (1,3).…”
mentioning
confidence: 99%